2009
DOI: 10.1002/cbic.200800716
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Glycoprofiling by Using Random Sequence Peptide Microarrays

Abstract: Current analytical methods have been slow in addressing the growing need for glyco-analysis. A new generation of more empirical high-throughput (HTP) tools is needed to aid the advance of this important field. To this end, we have developed a new HTP screening platform for identification of surface-immobilized peptides that specifically bind O-antigenic glycans of bacterial lipopolysaccharides (LPS). This method involves screening of random sequence peptide libraries in addressable high-density microarray form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Random sequence peptide arrays were produced as described in Morales Betanzos et al (11). Briefly, 10 K random 17-mer sequences containing equal probability of the 20 amino acids except cysteine were generated.…”
Section: Methodsmentioning
confidence: 99%
“…Random sequence peptide arrays were produced as described in Morales Betanzos et al (11). Briefly, 10 K random 17-mer sequences containing equal probability of the 20 amino acids except cysteine were generated.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of each peptide is known, but generated by a random number generator using 19 aa (cysteine was omitted). We found that the (3-aminopropyl)triethoxysilane (APTES) microarray surface chemistry used in earlier published reports of screening proteins, antibodies and carbohydrates [18], [23][25] showed high levels of non-specific binding to the interstitial regions of the array and low level binding to peptide spots when whole bacterial cells were screened. To address these issues we developed an alternative microarray surface chemistry using a hyperbranched polymer that reduced non-specific binding and increased the peptide density (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…This technology has been used in other studies to determine binding patterns specific to that disease, such as Alzheimer’s [16], and we expect that for each disease there will be a different binding pattern that could allow us to distinguish one illness from another ([32,33] and unpublished data). In the future, it would be good to test our microarray technology on other autoimmune diseases to ensure that our tests can distinguish one autoimmune disease from another.…”
Section: Discussionmentioning
confidence: 99%